Prevalence of Hepatitis B virus infection among blood donors at Nakasero blood bank, Kampala district. A cross-sectional study. - Nekesa, Racheal; Kafero, Emmanuel; Nansereko, Hasifah; Ssemuwemba, Franscisco; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2026)
Background: Hepatitis B virus (HBV) remains a major global public health concern, causing chronic infections, cirrhosis, and hepatocellular carcinoma despite available vaccines. This study examined the prevalence of hepatitis B virus infection among blood donors at Nakasero blood bank kampala district. Methodology: A cross-sectional study was conducted at Uganda Blood Transfusion Services (UBTS), Nakasero, Kampala District. A total of 150 voluntary blood donors, aged 18–60 years, who consented to participate, were included. Participants were selected using purposive, simple random, and systematic sampling techniques. Data were analyzed using SPSS v20.0, with results presented as frequencies and percentages. Results: The overall HBV prevalence was 15% (23/150), higher among males (8.6%) than females (6.6%). Among 150 donors, 67.3% were male and 32.7% female, with the majority aged 18–25 years (51.3%). The most affected age group was 26–35 years (52%), followed by 18–25 years (29.3%). Key risk factors included alcohol use (58%), multiple sexual partners (54%), dental surgery history (38.6%), and cohabitation with an HBV-positive individual (40.6%). Knowledge about HBV transmission and prevention was moderate, with 54.7% having ever heard of HBV and 64.7% reporting vaccination. Conclusion: HBV remains prevalent among blood donors at Nakasero Blood Bank, with higher rates among males and specific age groups. Behavioral and knowledge-related factors contribute significantly to HBV risk. Recommendations: Routine and mandatory HBV screening for blood donors should be enforced. Public health campaigns to raise awareness about HBV transmission and prevention, along with expanded vaccination coverage, are essential.